Factors in Improving the Safety of Railway Level Crossing Infrastructure in Indonesia - Kresna Bayu Mahaputera; Jojok Widodo Soetjipto; Erno Widayanto (Eduvest - Journal of Universal Studies, 2026)
Railway level crossings in Indonesia remain significant accident-prone areas, contributing to nearly 70% of total railway incidents. Various solutions have been implemented to reduce the risk of accidents at level crossings, including converting them into non-level crossings. However, selecting the most appropriate infrastructure alternative is often challenging because it involves multiple factors, making the process time-consuming and prone to conflict. This study aims to identify and rank the factors influencing improvements in level crossing infrastructure safety using a descriptive-analytical approach. Five main criteria are established in this study—safety, technical, economic, environmental, and social—which are further divided into several relevant sub-criteria based on previous literature. Data were collected through questionnaires distributed to nine expert respondents from government agencies, railway operators, and consulting firms. The results show that accident history, structural durability, maintenance costs, sustainable drainage, and traffic impacts are the most prioritized factors. These findings highlight the need for a quantitative, holistic, and multidimensional approach to decision-making, considering the high level of complexity and potential conflicts of interest among stakeholders. This research provides a foundation for formulating more objective and sustainable policies in designing future alternatives for non-level crossing infrastructure.